2003
DOI: 10.1021/ja028867f
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Activation by Nonheme Iron(II) Complexes: α-Keto Carboxylate versus Carboxylate

Abstract: Mononuclear iron(II) alpha-keto carboxylate and carboxylate compounds of the sterically hindered tridentate face-capping ligand Tp(Ph2) (Tp(Ph2) = hydrotris(3,5-diphenylpyrazol-1-yl)borate) were prepared as models for the active sites of nonheme iron oxygenases. The structures of an aliphatic alpha-keto carboxylate complex, [Fe(II)(Tp(Ph2))(O(2)CC(O)CH(3))], and the carboxylate complexes [Fe(II)(Tp(Ph2))(OBz)] and [Fe(II)(Tp(Ph2))(OAc)(3,5-Ph(2)pzH)] were determined by single-crystal X-ray diffraction, all of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
181
7
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(223 citation statements)
references
References 102 publications
32
181
7
3
Order By: Relevance
“…Such species have been found in the reactions of O 2 with heme proteins and models (6,7) as well as with one copper enzyme (8) and several synthetic copper and nickel complexes (9)(10)(11)(12)(13)(14)(15)(16). Such species have also been invoked in the mechanisms for nonheme iron enzymes, but only indirect evidence has been obtained to date (39)(40)(41). The best evidence derives from the observed formation of Fe-NO adducts analogous to the related iron-superoxo complexes in the enzyme mechanisms (42)(43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 95%
“…Such species have been found in the reactions of O 2 with heme proteins and models (6,7) as well as with one copper enzyme (8) and several synthetic copper and nickel complexes (9)(10)(11)(12)(13)(14)(15)(16). Such species have also been invoked in the mechanisms for nonheme iron enzymes, but only indirect evidence has been obtained to date (39)(40)(41). The best evidence derives from the observed formation of Fe-NO adducts analogous to the related iron-superoxo complexes in the enzyme mechanisms (42)(43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 95%
“…1) [6,7]. The incorporation of oxygen from dioxygen into the alcohol product during hydroxylation reactions by this class of enzymes is well documented [8]. Further, incubations of prokaryotic 2OG oxygenases under an 18 O 2 atmosphere have demonstrated that, during hydroxylation reactions, a less than stoichiometric incorporation of oxygen into the hydroxyl group of the product can occur in some cases (e.g., hydroxylation of some substrates catalysed by clavaminic acid synthase and deacetoxy/deacetyl cephalosporin C synthase) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism has served well as a general working hypothesis for the mechanisms of all of the ␣KG-dependent dioxygenases: extensive studies on several family members, and inorganic models thereof have failed to reveal significant inconsistencies (1)(2)(3)(26)(27)(28)(29)(30)(31). However, the first direct evidence for any of the several oxidized iron intermediates invoked in this mechanism came relatively recently, with the detection by stopped-flow (SF) absorption and freeze-quench (FQ) Mössbauer spectroscopies of two transient states in the catalytic cycle of taurine:␣KG dioxygenase (TauD) (see Scheme 1) (32).…”
mentioning
confidence: 99%